The Influence of ANEKA-Based Character Integrated in Physics Course with E-learning Schoology - Hilyana, F. Shoufika; Masfuah, Siti (Department of Science Education, Universitas Sultan Ageng Tirtayasa, 2018)
The development of technology has brought enormous changes to the progress of education world. The form of the technology is E-Learning, with platform that can be used as an interactive learning media is Schoology, it’s expected that lecturers can actualize the basic values ANEKA (accountability, nationalism, public ethics, quality commitment, and anti corruption). The purpose to know the influence of characters education based on ANEKA in courses Technical Physics with e-learning Schoology. The research method is quantitative with quasi experiment, the population is Electrical Engineering students at UMK. Experimental variable is the treatment for experimental class (e-learning schoology), and control class (conventional), the dependent variable is ANEKA-based characters. The result of ANEKA-based characters obtained with increase before and after treatment. The characters value is highest in nationalism, and least of quality commitment. The analysis of experimental class increase of 4.59, and the control class of 2.68. Result of ANEKA-based characters from control and experimental class get significant 0.000 (<0,05) which means that the application of learning in the Physics courses by e-learning schoology can increase higher by 25% than the conventional learning by 16%.